Striking Perturbations of Ionospheric Total Electron Content (TEC) During Earthquake - Al-Ubaidi, Najat; Ali, Isra’a (Iraqi Journal of Science, 2023)
To study the striking perturbations of ionospheric Total Electron Content (TEC) before, during, and after the earthquake (M≥5) for earlier prediction to avoid calamities, ionospheric TEC data are taken by using red shift technique from two-frequencies GPS signals.. Tohoku earthquake on 11th March 2011 is chosen as case of our study (A magnitude M9.0 earthquake reported by the US Geological Survey gives its origin time at 05:46:23 UTC; the epicenter was located at 38.322oN, 142.369oE of the east coast of Honshu). The study was made 15 days before and 15 days after earthquake occurred over Japan at four different geographic positions, Kokubunji (35.7oN, 139.5oE), Wakkanai (45.2oN, 141.8oE), Yamagawa (31.2oN, 130.6oE) and Okinawa (26.7oN, 128.2oE). Observations TEC values compared with predicted TEC values by using the International Reference Ionosphere (IRI 2007) model to study the accuracy of model during the earthquake. Finally absolute error calculated between observed TEC (Obs.) values and predicted (Pre.) values before and after correction for 24 hours, which is reveals fewer errors after correction.